Climate adaptation in Kenya: Narratives and frames shaping policy and practice - Ouma, Marion (Nordiska Afrikainstitutet, 2023)
Climate change poses one of the greatest challenges of our time with the impact severely distressing lives and livelihoods particularly in countries of the Global South. In Kenya, climate-related disasters and extreme events have plagued the most vulnerable communities with the most affected as marginalized communities. Through the institutionalization of the Kenya Climate Change Act (2016), the government provides guidance for the climate change response, proposing measures to build resilience and enhance adaptation. Efforts to promote adaption and resilience of communities and households often involve multi-pronged approaches promoted through multi-actor and multi-level action. Besides the provisions of the Act., climate adaptation discourse in the country is shaped through particular narratives which have both international and national contexts. The narratives have developed over time and often overlap, with institutions and individuals working across the different frames. In this paper, we review literature on climate adaptation in Kenya and use it to discuss four of the dominant narratives that shape climate change adaption in the country. The narratives discussed in this paper relate to adaptive capacities, technological and technical, gender and feminist, and climate justice framings. We argue that some narratives have been dominant in shaping adaptation discourse and practice towards certain solutions, and in turn may have obscured and/or subsumed other plausible solutions.